The Impact of ACIK Gymnastics on Physical Fitness in Elementary Schools - Noviria Sukmawati; Dewi Septaliza; Aprizal Fikri; Selvi Atesya Kesumawati (UNIB Press, 2022)
Physical fitness is a condition that every child must have. Children who have good physical fitness show healthiness. To have good physical fitness can be done by exercising. One sport that is easy for children to do is gymnastics. This study was aimed to determine the impact of ACIK gymnastics on children in elementary schools. This study was supposed to determine the impact of gymnastics on the physical fitness of children aged between 6-9 years. This type of research was experimental research by providing treatment in the form of ACIK gymnastics to children. The sample used in this study was 30 girls at SD 01 Kandis Ogan Ilir. The data were obtained from the results of the pretest and posttest. This research was an experimental research. Statistical test using SPSS means the value of Sig. (2 tailed) is 0.002 <0.05, then Ho is rejected and Ha is accepted. So it can be concluded that there is a difference in the average pre-test and post-test TKJI test results, which means that there is an effect of ACIK gymnastics on the physical fitness of children at SD Negeri 10 Kandis. Based on data analysis and discussion, it can be concluded that gymnastics has a significant impact on increasing physical fitness in early childhood. It can be suggested that ACIK gymnastics can be used in physical activities as well as exercises to improve fitness because of it.